Auricular therapy for polycystic ovary syndrome: A protocol for a systematic review and meta-analysis. Issue 49 (4th December 2020) - Li, Yangyang; Zheng, Xiaoying; Wang, Yingji; Li, Yan
Abstract: Background: This systematic review protocol aims to describe a meta-analysis to assess the effectiveness and safety of auricular therapy for patients with polycystic ovary syndrome (PCOS). Methods: Randomized controlled trials of auricular therapy in treating PCOS will be searched in PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Wan-Fang Database, and Chinese Scientific Journal Database. The primary outcome is the body mass index. The study selection, data extraction, and study quality evaluation will be performed independently by 2 researchers. A meta-analysis will be performed using RevMan V5.3 statistical software if possible; otherwise, descriptive analysis or subgroup analysis will be conducted. The quality of evidence for outcomes will be assessed with the Grading of Recommendations Assessment, Development and Evaluation approach. Results: This study will evaluate the effect and safety of auricular therapy in treating PCOS. Conclusions: The evidence we generated from the present study will provide more options for PCOS management in clinical practice. The registration DOI: 10.17605/OSF.IO/VBPSM.